Neural correlates of response bias: Larger hippocampal volume correlates with symptom aggravation in combat-related posttraumatic stress disorder. (30th September 2018) - Butler, Oisin; Herr, Kerstin; Willmund, Gerd; Gallinat, Jürgen; Zimmermann, Peter; Kühn, Simone
Highlights: PTSD is vulnerable to malingering as diagnosis is based on self-reported symptoms and is often associated with personal or financial gain. In PTSD neuroimaging research, methods to ensure the validity of a clinical diagnosis, such as the use of symptom validity tests, are rarely applied. The potential impact of including malingers along with credible PTSD patients on results is unknown. We compare gray matter volume in malingerers and credible PTSD patients. Malingerers display larger gray matter volumes in regions involved in PTSD, inhibition and deception, including the hippocampus. Findings emphasize the need to distinguish malingerers from credible patients to ensure the robustness and reliability of experimental results. Abstract: The diagnosis of posttraumatic stress disorder (PTSD) is vulnerable to the simulation or exaggeration of symptoms as it depends on the individual's self-report of symptoms. The use of symptom validity tests is recommended to detect malingering in PTSD. However, in neuroimaging research, PTSD diagnosis is often taken at face validity. To date, no neuroimaging study has compared credible PTSD patients with those identified as malingering, and the potential impacts of including malingerers along with credible patients on results is unclear. We classified male patients with combat-related PTSD as either credible ( n = 37) or malingerers ( n = 9) based on the Morel Emotional Numbing Test and compared structural neuroimaging and psychological questionnaire data. Patients identified as malingerers had larger gray matter volumes in the hippocampus, right inferior frontal gyrus and thalamus, and reported higher PTSD symptoms than credible PTSD patients. This is the first structural neuroimaging study to compare credible PTSD patients and malingerers. We find evidence of structural differences between these groups, in regions implicated in PTSD, inhibition and deception. These results emphasize the need for the inclusion of SVTs in neuroimaging studies of PTSD to ensure future findings are not confounded by an unknown mix of valid PTSD patients and malingerers.